Measuring Organizational Performance and The Role of Performance Management Using Profitability Ratio - Setiawati, Eka; Ngamal, Yohanes (Syntax Literate, 2024)
The purpose of this research is to find out how PT. X applies performance management and performance as a measuring tool. The data collection method in this research is library research. In its implementation, Library Research is carried out by reading, studying and taking notes on various literature or reading materials that are appropriate to the subject matter, then filtered and outlined in a theoretical framework of thought." (Kartini Kartono: 1998). The conclusion that can be drawn is Company PT X in the 2018-2022 period there were increases and decreases, this condition was related to Covid 19 where external factors such as the occurrence of Covid 19. The highest profitability occurred in 2018. By looking at these data, the performance of the PT company can be assessed. X is good. Because PT X controlling the cost of goods or production costs, and PT X from the profitability ratio description has been able to produce efficiently.